Leukocyte Mitochondrial DNA Copy Number and Risk of Thyroid Cancer: A Two-Stage Case-Control Study - Zheng, Jian; Cui, Ning-hua; Zhang, Shuai; Wang, Xue-bin; Ming, Liang (Frontiers in Endocrinology, 2019)
Background: Mitochondrial DNA copy number (mtDNA-CN) may contribute to the development of various cancer types in a tumor-specific manner. However, little is known about whether leukocyte mtDNA content confers susceptibility to thyroid cancer (TC). This study aimed to investigate the associations of leukocyte mtDNA-CN with the risk and clinicopathological features of TC in a Chinese population. Methods: In this two-stage case-control study with a total of 402 TC patients and 406 controls, leukocyte mtDNA-CN content was measured with a quantitative PCR method. In a subset of 100 cases and 100 controls, levels of leukocyte 8-hydroxy-2′-deoxyguanosine (8-OHdG) and plasma malondialdehyde, as two biomarkers for oxidative stress, were determined by ELISA and colorimetric kits, respectively. Results: In a combined analysis of discovery and validation sets, high mtDNA-CN content was positively associated with increased TC risk, after adjusting for confounders (OR for per SD increment: 1.43; 95%CI, 1.23-1.66; P < 0.001; OR for tertile 3 vs tertile 1: 2.10; 95%CI, 1.48-3.00; Ptrend < 0.001). This linear dose-response relationship was more pronounced in subtype analyses for papillary and follicular thyroid carcinoma (P < 0.001 for all), as well as in subgroup analyses for subjects with overweight and obesity (Pinteraction = 0.015). In TC patient, we observed the positive correlations of mtDNA-CN with advanced TNM stage (P = 0.006) and the presence of lymph node metastasis (P = 0.012). Leukocyte mtDNA-CN content was also identified to increase with the levels of leukocyte 8-OHdG (P < 0.001), a biomarker for oxidative DNA damage. Conclusion: Our data suggest that the increase in leukocyte mtDNA-CN content may correlate with oxidative DNA damage, and serve as an independent risk factor for TC.